MANAJEMEN PERPUSTAKAAN DI MAN 2 PARINGIN - Miranti Miranti (CV. ADIBA AISHA AMIRA, 2025)
Good library management is highly expected, because with good existing management it will support better school performance, so that the vision and mission of the school can be realized. Based on this statement, the formulation of the problem in this study is how is the library management at MAN 2 Paringin? and what are the obstacles it faces? The goal to be achieved is to find out the library management at MAN 2 Paringin and the constraints it faces. This type of research is field research and the approach taken is a qualitative approach. The object of this research is library management at MAN 2 Paringin. The subjects of this study were the head of the madrasa and the librarian at MAN 2 Paringin. The data collection techniques are carried out by means of interviews, observation and documentaries. Data processing techniques using data reduction, data display and data verification and data analysis using descriptive qualitative. The results of this study indicate that 1) Library Management at MAN 2 Paringin is good, including; First; Planning (Planning). This can be seen from the formulation in the library work plan. Second; Organizing (Organizing). This can also be seen from the existing organization. Third; Actuating. The head of MAN 2 Paringin has mobilized his citizens (students and teachers) to visit the library. In its service, the library provides services (open- access) meaning that users choose directly and take their own time to read or borrow books. Technical services include cataloging, labeling, and displaying library materials. And information services include circulation, reference and audio-visual. Fourth; Supervision (Controlling). The head of MAN 2 Paringin has supervised library activities every day. 2) Constraints, such as funds for procuring books and supporting facilities are limited, so the execution is slow/slow. In addition, some students do not understand how to use or use the facilities in the library. Where they don't maintain its durability, such as books not being returned to their places, reading tables scribbled on, fans being played with, air conditioners are also the same, so books or existing facilities are easily or quickly damaged. The solution to overcome these obstacles is to carry out regular maintenance and cooperate with educational institutions, companies or the government to obtain procurement funds.